Study of safety culture in healthcare institutions: case of an Algerian hospital - A BOUGHABA; S ABERKANE; Y FOURAR; M DJBABRA (International Journal of Health Care Quality Assurance, 2019)
Purpose For many years, the concept of safety culture has attracted researchers from all over the world, and more particularly in the area of healthcare services. The purpose of this paper is to measure safety culture dimensions in order to improve and promote healthcare in Algeria. Design/methodology/approach The used approach consists of getting a better understanding of healthcare safety culture (HSC) by measuring the perception of healthcare professionals in order to guide promotion actions. For this, the Hospital Survey on Patient Safety Culture questionnaire was used in a pilot hospital setting where it was distributed on a number of 114 health professionals chosen by stratified random sampling. Findings The results showed that the identified priority areas for HSC improvement help in establishing a trust culture and a non-punitive environment based on the system and not on the individual. Originality/value Safety is recognized as a key aspect of service quality, thus measuring the HSC can help establish an improvement plan. In Algerian health facilities, this study is considered the first to examine perceptions in this particular area. The current results provide a baseline of strengths and opportunities for healthcare safety improvement, allowing the managers of this type of facilities to take steps that are more effective.